Ethno-ecology of Komplangan Field of the Bromo, Tengger, and Semeru Area in East Java:A Qualitative Approach - Jati Batoro; Serafinah Indriyani; Bagyo Yanuwiadi (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
This research supports the sustainable environmental development, especially at Perhutani area. The objective of this ethno-ecological study was to know relationship between daily life of local people related to their agroforestry practices in edge of the forest belong to Perhutani at the landscape of Bromo Tengger Semeru-East Java. The Non-Timber Forest Products (NTFPs) showed the importance of the forest for the local people. This study covered the perception and conception traditional management system of environment by the local society and also impact of their activities. Data were collected by applying ethno-ecology research methods. Quality of data were measured by means of participatory ethno-botanical appraisal (PEA) and some research methods included semi-structural and open discussion, in-deep interview, direct observation and plants identification. The results showed that development and management of the natural resources, in Komplangan agroforestry, were highly related to the plant conservation policy. The land use system was adapted from indigenous knowledge which consisted of holly sites (Pedanyangan), worship sites (Sanggar Pamujan), cemetery area and terrace. The conservation model and traditional knowledge in agricultural practices could be used as a model of komplangan area which should be taken into account as the key of biodiversity conservation. Traditional knowledge from these integrative studies will support the sustainable development of NTFPs.